The shapes of wine and table grape leaves: An ampelometric study inspired by the methods of Pierre Galet - Daniel H. Chitwood (Plants, People, Planet, 2021)
Societal Impact Statement Leaf shapes are critical to the identification of grapevine varieties. Historically, measures of grapevine leaves were used to enforce appellation law and leaf shape is used to this day to distinguish economically important clones that genetic analyses fail to discriminate. The ampelometry (“vine” + “process of measuring”) of Pierre Galet (1921‐2019), through quantitative measurements and hand‐drawings, illuminated the beauty of grapevine diversity for the world. Here, mathematical methods rigorously quantifying hand‐drawings of grapevine leaves are presented, with implications for how we document and preserve the stunning diversity of plants we so readily see with our eyes. Summary People have an innate ability to recognize different patterns in among plants. Quantifying these differences, that we assimilate so effortlessly with our senses, is more challenging. Grapevines are a special case in which leaf shape has been critical to identify varieties correctly. The distinct morphology of grapevine leaves lends itself to the application of mathematical approaches that quantify shape. Here, corresponding points on every grapevine leaf (landmarks) and equidistant points between landmarks (pseudo‐landmarks) were used to capture intricate, local features in grapevine leaves: the curvature of veins, lobes, and sinuses and the shapes of serrations. Using these points, averaged leaf shapes for 60 varieties of wine and table grapes were calculated that quantify shape to the same resolution as hand drawings. The overall morphological similarity of each variety to the other classified the leaves into two discrete groups: (i) deeply lobed and (ii) more entire—corresponding to the measurements of sinus depth put forward by the ampelographer Pierre Galet. Using the system of Galet, landmarks, and pseudo‐landmarks were converted into relative distance and angle measurements. Using a high number of landmarks and pseudolandmarks increased the accuracy of predicting variety correctly, compared to using a finite number of landmarks alone. The ability to identify correctly a vine variety from leaf shape will have significant implications for the wine industry, from ensuring correct scion and rootstock plantings in vineyards, to enforcing appellation law to discerning clones that are genetically indistinguishable.